Overstating the value of the IUCN Red List for business decision‐making. Issue 3 (18th April 2018) - Burgass, Michael J.; Arlidge, William N.S.; Addison, Prue F.E.
Abstract: The relationship between business and conservation is growing increasingly closer, with the recognition that collaboration can lead to better outcomes for biodiversity. Bennun et al. introduce the IUCN Red List of Threatened Species (the Red List) to inform businesses' mitigation of biodiversity impacts; and subsequently how it can be improved to further increase its effectiveness. While we applaud this ever‐closer union of business and conservation, we believe the authors overinflate the value of the Red List in decision‐making, do not account for its limitations and therefore do not justify their conclusions for improving the Red List for business use. We are concerned this focus on wide application of the Red List promotes it as a "one‐stop‐shop" and could lead to discounting of more appropriate approaches.